Network formation with local complements and global substitutes: The case of R&D networks - Chih-sheng Hsieh; Michael D. König; Xiaodong Liu (University of Zurich, Department of Economics, 2017)
In this paper we introduce a stochastic network formation model where agents choose both actions and links. Neighbors in the network benefit from each other's action levels through local complementarities and there exists a global interaction effect reflecting a strategic substitutability in actions. The tractability of the model allows us to provide a complete equilibrium characterization in the form of a Gibbs measure, and we show that the structural features of equilibrium networks are consistent with empirically observed networks. We then use our equilibrium characterization to show that the model can be conveniently estimated even for large networks. The policy relevance is demonstrated with examples of firm exit, mergers and acquisitions and subsidies in the context of R&D collaboration networks.
Keywords: C11; C15; C63; C73; D83; D85; L22; 330; Network formation; peer effects; technology spillovers; key player; mergers and acquisitions; subsidies